Rhododendrol‐induced leukoderma update I: Clinical findings and treatment. Issue 7 (8th March 2021) - Matsunaga, Kayoko; Suzuki, Kayoko; Ito, Akiko; Tanemura, Atsushi; Abe, Yuko; Suzuki, Tamio; Yoshikawa, Momoko; Sumikawa, Yasuyuki; Yagami, Akiko; Masui, Yukiko; Inoue, Shintaro; Ito, Shosuke; et al.
Abstract: Individuals who used skin‐whitening cosmetics (quasi‐drugs) containing 2% rhododendrol‐containing agents, developed leukoderma at a higher frequency than those who have used other skin‐whitening cosmetics. The Rhododenol Research Team (RD‐Team) was formed and commissioned by Kanebo Cosmetics Inc. to conduct research in treatments of rhododendrol‐induced leukoderma (RDL), to evaluate effective treatment options from a medical standpoint, and provide information to a wide range of people. In this study, we evaluated the efficacy of various treatments for RDL from a medical perspective, based on the information published in the literature as original or review articles. We searched the PubMed (international) and the Igaku Chuo Zasshi (ICHUSHI) (Japanese) databases using the keywords "Rhododenol" and "rhododendrol", for articles published between July 2013 and November 2020. We discuss the main clinical findings and treatments (topical, oral, phototherapy, and surgical) of this condition based on the literature review. We found that ultraviolet light therapy is the most effective treatment for RDL. We have also summarized reports of the efficacy of oral vitamin D3 in RDL. A topical prostaglandin derivative has been reported in a new study to be effective. We have provided guidance for patients using self‐tanning and skin‐whitening agents to improve their quality of life. Finally, we have highlighted the importance of providing patients with information on contact dermatitis and instructing them to discontinue product use immediately if they develop any symptoms of contact dermatitis while using skin‐whitening agents.